2014
DOI: 10.1371/journal.pone.0115088
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Longitudinal and Interpersonal Continuity of Care with Emergency Department Use, Hospitalization, and Mortality among Medicare Beneficiaries

Abstract: BackgroundContinuity of medical care is widely believed to lead to better health outcomes and service utilization patterns for patients. Most continuity studies, however, have only used administrative claims to assess longitudinal continuity with a provider. As a result, little is known about how interpersonal continuity (the patient's experience at the visit) relates to improved health outcomes and service use.MethodsWe linked claims-based longitudinal continuity and survey-based self-reported interpersonal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 38 publications
6
60
0
2
Order By: Relevance
“…Optimal continuity of care is associated with decreased utilisation of EDs (12). Our results suggest an association between utilisation of multiple general practices and presentation to ED, in agreement with Wright and colleagues (7).…”
Section: Ed Utilisationsupporting
confidence: 91%
“…Optimal continuity of care is associated with decreased utilisation of EDs (12). Our results suggest an association between utilisation of multiple general practices and presentation to ED, in agreement with Wright and colleagues (7).…”
Section: Ed Utilisationsupporting
confidence: 91%
“…In a sensitivity analysis, the BB index score was divided into tertiles, not separating patients with scores of 0 and of 1. 24 The provider identification index 25 (see Supplementary Textbox 1, http://www.annfammed.org/content/15/6/515/suppl/DC1) requires an assigned clinician. The score for this index, which we termed appointed general practitioner index, is the proportion of visits during the study period to the general practitioner most recently visited before the index event of hospitalization for the case patients; we divided scores into quartiles.…”
Section: Measures Of Continuity Of Carementioning
confidence: 99%
“…While numerous previous studies have shown associations between CoC and a wide range of health outcomes, the majority of these have dichotomised measures of CoC using arbitrary cut-points (e.g. CoC 0.75) (13,16,18), or score percentiles (12,14), while others have used CoC as a continuous variable (7,15). In this study, individuals with 'high' continuity (CoC ≥0.75) comprised both those with the highest (UPC or CoC Index 0.75-0.99) and lowest (UPC or CoC Index 1.0) odds of emergency hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence suggests a beneficial effect of claimsbased CoC (11), mostly using density or dispersion measures, on health service utilisation (12)(13)(14)(15)(16), medication adherence (17), unnecessary medical procedures (7), cost (18) and health outcomes including mortality (12,19). However, little attention has been paid to further interrogating these associations, with most previous research assuming the linear effect of CoC on outcomes by treating this as a continuous (7,15) or a dichotomous variable (13,16,18).…”
Section: Introductionmentioning
confidence: 99%